A review of the subfamily Methochinae from Taiwan (Hymenoptera: Tiphiidae) with description of a new species and redescription of the known species - Narita, Keisuke; Mita, Toshiharu (Zootaxa, 2021)
Eleven species of Methocha Latreille from Taiwan are revised. Methocha cirrhocrus Narita & Mita, sp. nov. is described and illustrated. The previously unknown male of M. maai Lin, 1966 is described. Methocha taoi Lin, 1966 is newly synonymized under Methocha areolata Lin, 1966. The genus Karlissa Krombein, 1979 is newly recorded from Taiwan, and a new combination is proposed for Methoca (sic!) tricha Strand, 1913, which is transferred to the genus Karlissa Krombein. A key to the species based on males and females is given.